2012
DOI: 10.1016/j.cma.2011.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Numerical error estimation for nonlinear hyperbolic PDEs via nonlinear error transport

Abstract: The estimation of discretization error in numerical simulations is a key component in the development of uncertainty quantification. In particular, there exists a need for reliable, robust estimators for finite volume and finite difference discretizations of hyperbolic partial differential equations. The approach espoused here, often called the error transport approach in the literature, is to solve an auxiliary error equation concurrently with the primal governing equation to obtain a point-wise (cell-wise) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 27 publications
(84 reference statements)
0
19
0
1
Order By: Relevance
“…As a corollary, there are some combinations of (p, q, r) that are clearly more computationally expensive but less accurate, for instance the (2, 4, 6) scheme compared to the (2,4,4) scheme. It addition to the difference in accuracy, it was observed that the superconvergent (p < q = r) schemes produce differences in exact error and error estimate that are smoother, while the other schemes have difference in error that are dominated by high frequency behavior.…”
Section: Iiid Previous Results For Scalar Equationsmentioning
confidence: 96%
See 2 more Smart Citations
“…As a corollary, there are some combinations of (p, q, r) that are clearly more computationally expensive but less accurate, for instance the (2, 4, 6) scheme compared to the (2,4,4) scheme. It addition to the difference in accuracy, it was observed that the superconvergent (p < q = r) schemes produce differences in exact error and error estimate that are smoother, while the other schemes have difference in error that are dominated by high frequency behavior.…”
Section: Iiid Previous Results For Scalar Equationsmentioning
confidence: 96%
“…Results for a typical (2,4,4) scheme applied here is shown in Figure 5. Furthermore, using p < q = r for a randomly perturbed grid gives O(h r ) convergence for the error estimate, which agrees with the results obtained previously for scalar problems, with the (2, 4, 4) case shown in Figure 6a and the (2, 6, 6) case shown in Figure 6b.…”
Section: Ivb 1d Euler Equationsmentioning
confidence: 98%
See 1 more Smart Citation
“…For the curved, stretched, and perturbed classes of meshes it was found that the truncation error is in general zeroth order accurate. By incorporating the jump term coecient α, it was found that for the specic uniform mesh, a particular choice of 4 3 gives a fourth order truncation error, and this motivated the search of optimal jump term coecients that minimize truncation error and discretization error for the vertex-centered unstructured mesh case.…”
Section: Discussionmentioning
confidence: 99%
“…It can be shown 3 that for the special case of a linear dierential operator L, the truncation error τ can be used to calculate the discretization error ε, as L(ε) = τ, (1) known as the error transport equation. For a general nonlinear dierential operator, Banks et al 4 noted that the error transport equation takes another form dierent from simply replacing L by N in Eq. (1).…”
Section: Introductionmentioning
confidence: 99%